What lessons can innovation education learn from childhood and adolescent education of the Nobel Prize winners in chemistry?. Issue 2 (2017) - Shavinina, Larisa V.
Nobel Prize is the highest achievement and lessons from Nobel laureates are of great value for fostering the next generation of scientific innovators. This paper presents some findings from the project about early childhood and adolescent education of the Nobel Prize winners in chemistry. It considers the important role of 'nuclear' and extended families in nurturing innovators-geniuses, the availability of at least one outstanding teacher, who had a great impact on developing talents, and of good schools, as well as an evidence of academic acceleration. Early interest in science and the three other interests - reading, sports, and music - of Nobel laureates-to-be were identified, as well as their high curiosity, love to learn, and easiness in learning. These findings will be compared with the main conclusions from a similar study of Nobel laureates in physics published earlier. The implications for innovation education are of exceptional importance for cultivating tomorrow's geniuses of Nobel caliber.